2007
DOI: 10.1152/physiolgenomics.00173.2007
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 (R577X) genotype is associated with fiber type distribution

Abstract: is a Z-disc structural protein found only in type II muscle fibers. The X allele of the R577X polymorphism in the ACTN3 gene results in a premature stop codon and ␣-actinin-3 deficiency in XX homozygotes. Associations between the R577X polymorphism and the muscle-power performance of elite athletes have been described earlier. About 45% of the fiber type proportions are determined by genetic factors. The ACTN3 variant could be one of the contributing genes in the heritability of fiber type distribution through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
280
5
16

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(323 citation statements)
references
References 24 publications
22
280
5
16
Order By: Relevance
“…We genotyped this SNP in a limited sample (N¼16) from an independent study conducted in our research center from which muscle tissue biopsies were available. 24 Relative expression levels were 0.93 ± 0.18 and 0.95 ± 0.25 for AA homozygotes and G-allele carriers, respectively, and did not differ significantly (P¼0.80).…”
Section: Quantification Of Mrna Expressionmentioning
confidence: 95%
See 1 more Smart Citation
“…We genotyped this SNP in a limited sample (N¼16) from an independent study conducted in our research center from which muscle tissue biopsies were available. 24 Relative expression levels were 0.93 ± 0.18 and 0.95 ± 0.25 for AA homozygotes and G-allele carriers, respectively, and did not differ significantly (P¼0.80).…”
Section: Quantification Of Mrna Expressionmentioning
confidence: 95%
“…24 A detailed description of the mRNA extraction and real-time PCR chr12q12-14 fine mapping: ACVR1B and muscle strength A Windelinckx et al protocol for ACVR1B mRNA expression is available in Supplementary file 1 and elsewhere. 25 …”
Section: Quantification Of Acvr1b Mrna Expressionmentioning
confidence: 99%
“…76,78,80,82,106 Of those studies, only Walsh et al 78 and Zempo et al 106 found evidence of an association between muscle size and the ACTN3 null X allele, indicating at best a minor role for this polymorphism in explaining interindividual variability in this trait.…”
Section: Actn3mentioning
confidence: 99%
“…Na linha Z, as α-actininas são componentes primordiais, pois se ligam aos filamentos de actina de sarcômeros adjacentes, cumprindo a função de ancoragem dos filamentos finos e formando uma estrutura estabilizadora do tecido muscular durante a contração 20 . Adicionalmente à sua função na organização estrutural do sarcômero, estudos recentes sugerem que as α-actininas sarcoméricas também atuam na regulação do processo contrátil, na regulação do metabolismo energético e possivelmente, na determinação do tipo de fibra muscular 12,19,21 . Tal diversidade de função tem sido atribuída à grande capacidade que as α-actininas, em especial a isoforma -3, têm de se ligar a outras proteínas e outros elementos regulatórios intracelulares 22 .…”
unclassified
“…Vale salientar que as calsarcinas localizam-se na linha Z e apresentam-se ligadas à calcineurina, uma proteína Ca2+ CaM-dependente, um importante sinalizador muscular que exerce relevante papel na determinação do tipo de fibra 26 e na hipertrofia 27 . Devido a essa interação com a calcineurina, Vincent et al 21 investigaram a relação entre a porcentagem dos tipos de fibra muscular e a ausência de α-actinina-3. Os resultados mostraram que indivíduos com o genótipo RR (expressão da forma funcional da α-actinina-3) apresentaram maior porcentagem de fibras tipo IIx (14±2%) em relação a indivíduos XX (expressão da forma truncada) (9±1%).…”
unclassified